Brief itinerary of the Theater of Objects: history and main aspects (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This work focuses on the history of theater of objects, as well as its dissemination throughout Europe and Brazil through artist exchanges, laboratories, and theater festivals. The article also outlines a brief itinerary of the object in 20th Century Visual arts and Theater and presents some of the fundamental principles of theater of objects. These principles are not established as rigid norms, but as a collection of experiences, reports and reflections from artists linked to this manifestation.
Keywords: actor; object; puppetry; theater of objects; visual art